Pendidikan Jasmani dalam Meningkatkan Kesehatan Mental Remaja Siswa SMA Perkotaan (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to explain the role of physical education activities in supporting the mental health of high school adolescents in urban environments. This study uses a qualitative descriptive approach, with data collection techniques through in-depth interviews, observation of physical education learning activities, and review of documents related to school programmes. The data obtained were analysed using thematic analysis techniques to identify patterns, meanings, and connections between organised physical activities, such as sports games, fitness exercises, and motor activities, and the emotional, social, and psychological aspects of students. The results showed that regular participation in physical education helped students express themselves, manage stress, build self-confidence, strengthen social relationships, and balance academic demands and the need for activity. Overall, physical education played an important mediating role in promoting an active lifestyle and mental well-being among adolescents in urban areas.